Malaysia [International encyclopedia of laws on intellectual property law] - Abdul Ghani Azmi, Ida Madieha; Abdul Jalil, Juriah; Ismail, Suzi Fadhilah (Wolters Kluwer, 2018)
This encyclopedia summarises the law of intellectual property in Malaysia